Plan de mercadeo y proyecto de reestructuración administrativa y financiera de un club social, cultural, deportivo y beneficencia, caso: sociedad tungurahuense de Guayaquil. - Frías Flores, Brenda Cecilia (2009)
This project was developed in Guayaquil, its purpose is a financial and administrative reengineer, and the proposal of a marketing plan for a sport club, this is the case of “Sociedad Tungurahuense de Guayaquil”, where there was made in first place, a market research, consequently there was proposed a marketing mix, where product, service, price, place, promotion are being analized, with a sales and strategy promotion. There were used cash flows in order to get the differential cash flow, budget and forecasted financial statements, risk analysis using CAPM (Capital Asset Pricing Model), also, there were used TMAR, IRR and NPV, where it can be deduced that this is a viable project, showing a IRR=52.29% and a NPV=US$37,226, this analysis was made using a TMAR=29.44%. Finally a sensibility analysis was applied so it can be observed how a sales, costs and expenses variation affects the project. Sales can only support a decreasing of 3.35%, anything more than that will mean a non profitable project, costs can only increase a 24.5%, and operative expenses can increase a 5.35% so project can still be viable.